Aphid Biodiversity under Environmental Change Patterns and Processes - Kindlmann, Pavel.; Dixon, A.F.G.; Michaud, J.P. (Springer Netherlands : Imprint: Springer, 2010)
This book presents completely novel, yet unpublished findings on aphid population dynamics and ecology in the context of recent environmental changes and closely related issues. It can be used as complementary text in any course on population dynamics and ecology of crop pests at undergraduate or graduate levels. The book is intended mainly for graduate students, researchers in crop science, crop protection, agricultural advisors and managers, but it will surely attract attention of many other people interested in insect pests, their biological control and ecology.